Effects of jet grout on the performance of braced retaining walls - Ong, Chu Mei (Nanyang Technological University, 2020)
Over the years, due to land constraints, there is a significant increase in the number of projects going underground. It is hence common to see braced excavation during the construction of such projects. Many methods of soil improvement are used to ensure excavation is carried out safely and at a low construction cost. Therefore, this project will focus on evaluating the effects of jet grout on the performance of braced retaining walls. The jet grout (JGP) installed will help in soil improvement (stabilization). Finite element analysis was used to carry out the analysis where different thickness of jet grout layer is being installed into the soil. Several other parameters such as wall stiffness and JGP-wall adhesion factor were varied. A total of 24 cases were analysed. The maximum wall deflection, maximum wall bending moment and maximum strut forces were evaluated. Also, two additional cases with the final strut and final last two struts omitted were analysed separately to find out the influence on braced excavation with a reduced number of struts installed. The results showed that the increase in thickness of JGP will help to reduce the maximum bending moment of the wall, reduce the wall deflection and decrease the maximum strut forces. In the case with the final strut removed, the braced excavation can be successfully carried out with a lesser strut which can help to reduce the construction time. However, in the case where two final struts were removed, the braced excavation can only be carried with a large thickness of JGP installed to prevent the collapse of the excavation system.